FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA AUDITOR BPK RI PERWAKILAN PROVINSI BALI - Fembriani, Astrid; Budiartha, I Ketut (E-Jurnal Akuntansi, 2016)
The objective of this study was to prove the impact of audit structure, role conflict, role ambiguity, good governance comprehension, leadership style, organization culture and organization commitment to the performance of government auditors. The study took place in BPK RI Bali Provincial Representative. The data collected by questionnaire which involves 42 auditors were selected based on purposive sampling criteria as samples. The questionaires were spreads to 42 respondents, but only 39 respondents which the data could be processed. Technique of data analysis in this study was multiple linear regression. Hypothesis test with t test proves that the performance of government auditors influenced by audit structure, good governance comprehension, organization culture and organization commitment affect; but not influenced by role conflict, role ambiguity and leadership style. Keywords: the performance of government auditors, BPK RI bali provincial representatives
Keywords: kinerja auditor pemerintah, BPK RI perwakilan provinsi bali